(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article examines the concept of tourism as a socio-cultural phenomenon in the cultural space of the region. One of the promising regions in the field of tourism services development is the Republic of Karakalpakstan. Tourism in the republic has its own specifics due to the political peculiarities of the region. In these circumstances, it is considered important to develop new promising areas in the field of tourism.